Alterations of the miR-126-3p/POU2AF1/Spi-B Axis and JCPyV Reactivation in Multiple Sclerosis Patients Receiving Natalizumab - Mancuso, Roberta; Agostini, Simone; Hernis, Ambra; Caputo, Domenico; Galimberti, Daniela; Scarpini, Elio; Clerici, Mario (Frontiers in Neurology, 2022)
Natalizumab (NTZ) can reactivate human Polyomavirus JC (JCPyV) latent infection and lead to progressive multifocal leukoencephalopathy (PML). NTZ modulates the expression of miR-126-3p and its target genes, Spi-B, POU2AF1 and VCAM-1; Spi-B protein binds the JCPyV regulatory region, initiating early gene transcription. The aim of the present paper is the evaluation of miR-126-3p and soluble (s)VCAM-1 concentration, Spi-B/POU2AF1 gene expression, and JCPyV activity in MS patients before and during two-years NTZ. Serum miR-126-3p and sVCAM-1 concentration was measured before NTZ and after one, 12 and 24 months of treatment in 22 multiple sclerosis (MS) subjects, 1 patient who developed PML, and 29 healthy controls (HC). Spi-B and POU2AF1 expression in blood was analyzed at baseline and at month 24 in 13 MS patients; results were clusterized based on JCPyV activity. miR-126-3p was significantly down-regulated in MS before and during NTZ but was greatly increased in the PML patient. sVCAM-1 concentration was comparable in MS and HC, and was reduced by NTZ in MS and PML. Spi-B/POU2AF1 expression was significantly increased in MS at baseline and was upregulated by NTZ, particularly in JCPyV-infected patients in whom JCPyV reactivation was detected. Taken together, the results suggest that the modulation of the miR-126-3p/POU2AF1/Spi-B axis associates with JCPyV activity in NTZ-treated MS patients